Prevalence and determinants of adherence to oral adjuvant endocrine therapy among breast cancer patients in Singapore - Eskinder Eshetu Ali; Ka Lok Cheung; Chee Ping Lee; Jo Lene Leow; Kevin Yi-Lwern Yap; Lita Chew (Elsevier, 2017)
Objective: The success of oral adjuvant endocrine therapy (OAET) is greatly influenced by patients' level of adherence to treatment. The objective of this study is to measure the prevalence and determinants of adherence to OAET among breast cancer patients in Singapore. Methods: A cross-sectional survey of patients supplemented by analysis of their prescription records was used to collect data. Adherence to OAET was assessed using the Morisky Medication Adherence Scale-4 items and evaluation of refill gaps. Univariate and multivariate analyses were done to evaluate the association between patients' characteristics and adherence to OAET. Results: A total of 157 women who have started OAET at least 6 months before the time of interview participated in the study, of which less than half (64 patients, 40.8%) of the patients had high adherence. Univariate analysis identified patients who were 57 years or older (P = 0.027), unemployed (P = 0.027), on aromatase inhibitors (P = 0.023), on three or more concurrent medications (P = 0.001), and had one or more comorbidities (P = 0.000) to be significantly more adherent. However, only the number of comorbidities was found to be an independent predictor of adherence in a multiple logistic regression analysis (adjusted odds ratio = 2.60; 95% confidence interval = 1.208-5.593; P = 0.015). Forgetfulness was the main reason for nonadherence mentioned by 63 (67.7%) of the 93 nonadherent patients. Conclusions: Low level of OAET adherence was found in this study, and forgetfulness was cited as the main reason for nonadherence. Patients were generally receptive to the implementation of various strategies to assist them with their medication-taking behavior